Drug-eluting beads bronchial arterial chemoembolization vs. conventional bronchial arterial chemoembolization in the treatment of advanced non-small cell lung cancer - Yu, Guocan; Shen, Yanqin; Chen, Liangliang; Xu, Xudong; Yang, Jun (Frontiers in Medicine, 2023)
To compare the effectiveness and safety of drug-eluting bead bronchial artery chemoembolization (DEB-BACE) with conventional bronchial artery chemoembolization (cBACE) and provide a novel treatment option for advanced nonsmall cell lung cancer (NSCLC).Patients with advanced NSCLC underwent DEB-BACE or cBACE and were screened retrospectively. Progression-free survival (PFS) and overall survival (OS) were the primary outcome indicators, while technical success rate, objective response rate (ORR), disease control rate (DCR), and adverse events (AEs) were the secondary ones.Results: A total of 41 patients were enrolled in the study, 12 in the DEB-BACE group and 29 in the cBACE group, according to the treatment regimen. No patient achieved complete response. 18 patients achieved partial response (9 in each group), 15 patients achieved stable disease (3 in the DEB-BACE group and 12 in the cBACE group), and eight patients achieved progressive disease (all in the cBACE group) when treated for two months. The overall ORR and DCR were 43.9% (18/41) and 80.5% (33/41), respectively. ORR and DCR in the DEB-BACE group were 50.0% (9/12) and 100.0% (12/12), respectively, while ORR and DCR in the cBACE group were 31.0% (9/29) and 72.4% (21/29), respectively. Compared to cBACE, the ORR and DCR of DEB-BACE were significantly improved (P < 0.05). The median PFS was better in the DEB-BACE group than in the cBACE group (6.95 months vs. 3.20 months, respectively (Hazard Ratio [HR] = 0.416; P = 0.005). Furthermore, the median OS was significantly better in the DEB-BACE group than in the cBACE group (28.5 months vs. 22.5 months, respectively, HR = 0.316; P = 0.020).DEB-BACE has a good safety and therapeutic profile in advanced NSCLC and is superior to cBACE. DEB-BACE can be used as an alternative treatment option for advanced NSCLC, even in elderly patients.